Biorrefinaria da macroalga marinha Solieria filiformis (Gigartinales, Rhodophyta) para extração de R-ficoeritrina, iota-carragenana e valorização dos resíduos sólidos - Lima, Francisco Ewerton de Sousa (2022)
Solieria filiformis is a red seaweed abundant in the Brazilian coast. In the Ceara state it has been cultivated in the sea and its biomolecules have been extracted and studied by our research group. In the present study, a biorefinery scheme of S. filiformis biomass was proposed to extraction of R-phycoerythrin and iota-carrageenan, followed by use of the hydrolysated solid residue for protease production by Bacillus subtilis. The yields of the R-phycoerythrin and iota- carrageenan reached were 0.63 and 36.59 % dry seaweed. The purity index of the R-PE was 0.63 and 0.73 from aqueous extraction and freeze-thaw process. The iota-carrageenan extracted presented 44.07 % of carbohydrates, 3.41 % of proteins and 24.02 % sulfate. The cellulosic- rich solid waste was ac-id-thermal hydrolysated and presented 43.55 g/L of total carbohydrates, of which 12.91% were reducing sugars. The cultivation of Bacillus subtilis in acid hydrolysated generated 0.83 g/L of cell biomass and a proteolytic extract of 31.21, 30.89 and 29.94 U/mgP at pH 7, 9 and in presence of the soap, respectively. One protease of 21 kDa was revelated by SDS-PAGE in the supernatant. Thus, the S. filiformis biorrefinery was developed to produce important marine-derived ingredients for cosmeceuticals, nutraceuticals, and functional foods.